In silico Study on Structural Inhibition of Bacterial DNA Gyrase by Major Secondary Metabolites Found in Grape Seed Extract - Lawan, Haritha; Tharakee, Hashitha (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2023)
In the early 20th century, during the era of investigating and identifying essential â€œvitaminsâ€, scientific research focused on grape seed extracts and their bioactive components, particularly polyphenols. Extensive studies have demonstrated that grape seed extract, rich in proanthocyanidins, offers protection against a wide spectrum of diseases, encompassing inflammation, cardiac ailments, peptic ulcers, hypertension, diabetes, cancer, and microbial infections. To explore potential secondary metabolites within grape seed extract that could serve as structural inhibitors of bacterial DNA Gyrase, molecular docking studies were performed. The docking results revealed that two phytochemicals, namely (-)-catechin and Procyanidin-B2, exhibited the highest potency in inhibiting DNA gyrase subunit B. Subsequent in silico physicochemical and pharmacokinetic parameter predictions were conducted using specialized web servers for the examined phytochemicals. Notably, (-)-catechin displayed superior inhibitory and ADMET (Absorption, Distribution, Metabolism, Excretion, and Toxicity) characteristics, suggesting its potential for utilization in synthesizing novel antibacterial compounds.